Effect of periodic pile row in subway vibration Isolation. (2017) - Zhang, Shenglong; Wang, Wenbin; Wu, Zongzhen; Dai, Yuanting; Li, Yulu; Dai, Huaming
Abstract: At present measures for reducing vibration by subway are mainly from vibration source, path and building, where vibration isolation on path is an important one. This article studies the effect of periodic pile row in subway vibration Isolation for a planned building close to a subway in Beijing based on phonon crystal theory. First test the vibration of surface field and get the vibration characteristic frequency. Second calculate the attenuation zone of periodic pile row which contains the vibration characteristic frequency, and get the parameter combination of the pile. Third A track-tunnel-soil-building 3D finite element model was established by software ANSYS. Input the force of vibration source calculated by the model of vehicle and guideway coupling. Then use the finite model to calculate the effect of the periodic pile row. The result shows that the working frequency of the periodic pile row is higher than 12Hz. The Damping capacity of the largest Z vibration level is 4.13dB on the first floor, and the Damping capacity becomes greater with the increase of the floor. Periodic pile row based on phonon crystal has a wide vibration isolation frequency and a good vibration isolation performance.